Strategi Percepatan Penghapusan Kemiskinan Ekstrem di Provinsi Sulawesi Tengah: Pendekatan Konvergensi dan Inovasi Program - Dian Astuti (Yayasan Literasi Sains Indonesia, 2024)
Extreme poverty in Central Sulawesi remains a significant challenge that demands an integrated strategy. This study evaluates the effectiveness of government programs, including Gercep Gaskan Berdaya and PADUNGKU, in accelerating the eradication of extreme poverty. Secondary data from the 2023 P3KE Update and the 2024 BPS were analyzed using multiple linear regression. The findings reveal a 0.64% reduction in extreme poverty during the 2023-2024 period, with notable declines in Donggala (0.95%) and Poso (0.93%). The